Characteristics of Mixture fuel of Biodiesel from Waste Cooking Oil and Solar used as fuel in Diesel Engine - Susila Arita; Marwani Zahri Kadir; Siti Miskah (Journal of Mechanical Science and Engineering, 2013)
Abstract Biodiesel from waste oil fried food out of fuel can be used as an alternative to replaced diesel fuel or diesel. Biodiesel blended with diesel (B0) at the level of a certain ratio so obtained B5, B10, B15 and B20 (B5 is a mixture of 5% biodiesel and 95% diesel, etc.) is used as fuel in diesel engines. Then tested for their physical properties such as heating value, cetane number, and flash point. Performance compared to diesel engines that use diesel engines (B0). Engine operated on constant engine revolution in 1500, 1750, 2000, 2250 and 2500 rpm. From the test results in fact indicate that the B5 fuel to obtain the best performance of the engine at 2000 rpm (engine revolution).. At this engine revolution produced the lowest specific fuel consumption of 0.34 kg / kWh, thermal efficiency of 24.02%Â  while the effective power on all fuels are the same ie 1:26 kw . Â  Keywords: Biodiesel, cooking oil, diesel fuel, diesel engine